The impact of postgraduate studies on the teachers' practice. Issue 5 (19th October 2016) - Ion, Georgeta; Iucu, Romita
Abstract: This paper analyses the perceptions of teachers involved in postgraduate studies of the importance of their study programme for their profession, describes the benefits of postgraduate studies for their practice and examines the strategies used to enhance the impact research they undertake on their teaching. A questionnaire was administered to 161 teachers enrolled in master's and PhD programmes in schools of education of five research universities in Romania. The results demonstrate that postgraduate studies provide teachers with a crucial link between the research conducted and reported by faculties of education and their own work in schools. A large majority recognised that research conducted in universities had a personal impact, improving their teaching. Developing research projects involving both researchers and practitioners, reading about research findings in journals and enhancing communication between researchers and practitioners were reported as useful strategies that facilitated research utilisation in practice.